Energetic Basis for Exercise-Induced Pulmonary Congestion in Heart Failure With Preserved Ejection Fraction. Issue 21 (23rd November 2021) - Burrage, Matthew K.; Hundertmark, Moritz; Valkovič, Ladislav; Watson, William D.; Rayner, Jennifer; Sabharwal, Nikant; Ferreira, Vanessa M.; Neubauer, Stefan; Miller, Jack J.; Rider, Oliver J.; Lewis, Andrew J.M.
Abstract : Background: Transient pulmonary congestion during exercise is emerging as an important determinant of reduced exercise capacity in heart failure with preserved ejection fraction (HFpEF). We sought to determine whether an abnormal cardiac energetic state underpins this process. Methods: We recruited patients across the spectrum of diastolic dysfunction and HFpEF (controls, n=11; type 2 diabetes, n=9; HFpEF, n=14; and severe diastolic dysfunction attributable to cardiac amyloidosis, n=9). Cardiac energetics were measured using phosphorus spectroscopy to define the myocardial phosphocreatine to ATP ratio. Cardiac function was assessed by cardiovascular magnetic resonance cine imaging and echocardiography and lung water using magnetic resonance proton density mapping. Studies were performed at rest and during submaximal exercise using a magnetic resonance imaging ergometer. Results: Paralleling the stepwise decline in diastolic function across the groups (E/e′ ratio; P <0.001) was an increase in NT-proBNP (N-terminal pro-brain natriuretic peptide; P <0.001) and a reduction in phosphocreatine/ATP ratio (control, 2.15 [2.09, 2.29]; type 2 diabetes, 1.71 [1.61, 1.91]; HFpEF, 1.66 [1.44, 1.89]; cardiac amyloidosis, 1.30 [1.16, 1.53]; P <0.001). During 20-W exercise, lower left ventricular diastolic filling rates (r=0.58; P <0.001), lower left ventricular diastolic reserve (r=0.55; P <0.001), left atrial dilatation (r=–0.52; P <0.001), lower right ventricular contractile reserve (right ventricular ejection fraction change, r=0.57; P <0.001), and right atrial dilation (r=–0.71; P <0.001) were all linked to lower phosphocreatine/ATP ratio. Along with these changes, pulmonary proton density mapping revealed transient pulmonary congestion in patients with HFpEF (+4.4% [0.5, 6.4]; P =0.002) and cardiac amyloidosis (+6.4% [3.3, 10.0]; P =0.004), which was not seen in healthy controls (–0.1% [–1.9, 2.1]; P =0.89) or type 2 diabetes without HFpEF (+0.8% [–1.7, 1.9]; P =0.82). The development of exercise-induced pulmonary congestion was associated with lower phosphocreatine/ATP ratio (r=–0.43; P =0.004). Conclusions: A gradient of myocardial energetic deficit exists across the spectrum of HFpEF. Even at low workload, this energetic deficit is related to markedly abnormal exercise responses in all 4 cardiac chambers, which is associated with detectable pulmonary congestion. The findings support an energetic basis for transient pulmonary congestion in HFpEF. Abstract : Supplemental Digital Content is available in the text.